US Internal Medicine Program Director Perceptions of Alignment of Graduate Medical Education and Institutional Resources for Engaging Residents in Quality and Safety. (July 2018) - Chacko, Karen M.; Halvorsen, Andrew J.; Swenson, Sara L.; Wahi-Gururaj, Sandhya; Steinmann, Alwin F.; Call, Stephanie; Myers, Jennifer S.; Vidyarthi, Arpana; Arora, Vineet M.
Alignment between institutions and graduate medical education (GME) regarding quality and safety initiatives (QI) has not been measured. The objective was to determine US internal medicine residency program directors' (IM PDs) perceived resourcing for QI and alignment between GME and their institutions. A national survey of IM PDs was conducted in the Fall of 2013. Multivariable linear regression was used to test association between a novel Integration Score (IS) measuring alignment between GME and the institution via PD perceptions. The response rate was 72.6% (265/365). According to PDs, residents were highly engaged in QI (82%), but adequate funding (14%) and support personnel (37% to 61%) were lower. Higher IS correlated to reports of funding for QI (76.3% vs 54.5%, P = .012), QI personnel (67.3% vs 41.1%, P < .001), research experts (70.5% vs 50.0%, P < .001), and computer experts (69.0% vs 45.8%, P < .001) for QI assistance. Apparent mismatch between GME and institutional resources exists, and the IS may be useful in measuring GME–institutional leadership alignment in QI.